Pembelajaran Tahfiz Al-Quran pada Anak Usia Dini di Raudhatul Athfal Habibburrahman Alahan Anggang Kabupaten Agam - Miftahul Khairi; Nenny Mahyuddin (ANWARUL, 2024)
The tahfiz al-Quran activity is an activity of memorizing the Al-Quran. Learning tahfiz al-Quran aims to introduce children to the holy book from an early age and is also an effort to familiarize children with worshiping and preserving the Al-Quran. Learning tahfiz al-Quran consists of aspects of planning, implementation of learning and assessment. This research aims to describe how tahfiz Al-Quran is taught in early childhood at RA Habibburrahman. This type of research is qualitative descriptive research. This research was conducted at Raudhatul Atfhal Habibburrahman Alahan Anggang, Agam Regency. Data collection techniques use observation, interviews and documentation. The results of the research show: 1) the planning for tahfiz Al-Quran learning in the RPPH was not made in detail; 2) Tahfiz activities are carried out every day, every Friday the children repeat and display their memorization. Tahfiz activities are carried out by memorizing repeatedly and using several movements. The tahfiz activity is also repeated in each rak'ah of the dhuha prayer and before returning home from school there are several quizzes regarding memorization; 3) Daily assessment is carried out by observing children when they memorize reading and semester assessment is carried out by testing individual children regarding memorization for one semester and reported in a report card in the form of a checklist.